In silico-guided Molecular Docking Analysis of Doxorubicin with Low-density Lipoprotein - Jain, Sanjay K. (Asian Journal of Pharmaceutics (AJP), 2023)
Introduction: Brain tumor (BT), the most aggressive and difficult-to-treat malignancy, is the major cause of death in cancer patients. BT poses serious health concerns mainly because of their fast development and poor prognosis. BT includes a group of heterogeneous diseases, with unique biology that corresponds to the brain and its microenvironment. The brain contains many cell types distinct from those found elsewhere in the body, making it difficult to extrapolate the findings from brain cancers compared to other forms of cancer. Moreover, the anatomy of the brain presents challenges for treating both BTs and brain metastases. The brain is the hub of many proteins in which some of the proteins act as receptors for natural and synthetic ligands. Doxorubicin (DOX) is one of the most commonly used anticancerous drugs with high efficacy. Materials and Methods: In silico analysis provides key insights in designing effective drug delivery to the brain. Here, the molecular modeling package Schrödinger software was used to establish the specific interaction between DOX and low-density lipoprotein (LDL). Results and Discussion: DOX has good binding interactions (docking scores −8.526, −6.565, −6.667, and −7.040, respectively) with LDL (PDB ID: IN7D and 3M0C). The docking study of DOX found potent activity against BT with docking scores of −8.526, −6.565, −6.667, and −7.040. Conclusion: The present study may help medicinal scientists to formulate potent formulation against LDL receptor for BT targeting.